2018
DOI: 10.9734/jesbs/2018/40999
|View full text |Cite
|
Sign up to set email alerts
|

From Access to Quality Secondary Education: Developing Language Supportive Textbooks to Enhance Teaching and Learning of Biology Subject in Tanzania

Abstract: This paper reports findings from the development of Language Supportive Biology Textbook (LSBT) for Form I students in Tanzanian secondary schools to address the challenge of language barrier to learning. The LSBT was thus developed to facilitate smooth transition from Kiswahili to English language medium of instruction in learning Biology. The study used a participatory action research design that involved 2 experts from Tanzania Institute of Education (TIE), 2 Biology specialists from universities, 1 languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Results collected from pre-test revealed that biology teachers could not manage to set language objectives to be achieved in class. The reason behind can well be explained by lack of such important element in the current Tanzania biology syllabus (MoEVT, 2010), teachers' expertise and teaching and learning resources (Gabrieli, Sane, & Alphonce, 2018). In teachers' expertise aspect, the challenge was on the identification of content and language specific objectives.…”
Section: Discussion Biology Language Supportive Lesson Planningmentioning
confidence: 99%
See 4 more Smart Citations
“…Results collected from pre-test revealed that biology teachers could not manage to set language objectives to be achieved in class. The reason behind can well be explained by lack of such important element in the current Tanzania biology syllabus (MoEVT, 2010), teachers' expertise and teaching and learning resources (Gabrieli, Sane, & Alphonce, 2018). In teachers' expertise aspect, the challenge was on the identification of content and language specific objectives.…”
Section: Discussion Biology Language Supportive Lesson Planningmentioning
confidence: 99%
“…The choice of Dodoma was justified by the fact that it ranked among the regions which had poor performance in biology subject in form four National examinations in past 6 years (MoEVT, 2014b , MoEST, 2015, 20162018, 2019. One of the courses of this poor performance was ascertained to be the lack of teaching and learning resources and language of instruction (Gabrieli, Sane, & Alphonce, 2018).…”
Section: Area Of Studymentioning
confidence: 99%
See 3 more Smart Citations